Correlation between the cytokine profile and anticongestive medication in patients with chronic chagasic cardiopathy - Rodrigo Cunha de Sousa; Diego Bernardo de Deus; Thiago Álvares da Costa; Marcos Vinícius da Silva; Virmondes Rodrigues Junior; Dalmo Correia (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: Chronic chagasic cardiopathy (CCC) is essentially a dilated cardiomyopathy in which a subacute, but constant chronic inflammatory process causes progressive destruction of the heart tissue. The action of proinflammatory cytokines, such as tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), and anti-inflammatory cytokines, like interleukin IL-10 and IL-17, plays a fundamental role in the immunopathogenesis and evolution of disease. Early anti-congestive therapy, aimed at changing the morbidity and mortality rate, has been shown to reduce disease progression and to alter patients’ immune response pattern. METHODS: This cross-sectional study aimed to evaluate the profile of Th1 and Th17 cytokines and IL-17, TNF-α, and IFN-γ expressions in different stages of CCC. Forty patients affected by chronic Chagas disease were divided into different groups according to the stage of the pathology. In agreement with the Brazilian consensus on Chagas disease, patients were classified as presenting an undetermined form, a cardiac form and a digestive form. Serum IFN-γ, TNF-α, IL-10, and IL-17 were evaluated. RESULTS: Lower serum IFN-γ concentrations were detected in patients receiving angiotensin-converting enzyme inhibitors (p = 0.0182), but not in those using angiotensin receptor blockers (p = 0.0783). Patients using amiodarone and aldosterone antagonist presented higher serum TNF-α concentrations (p = 0.0106 and 0.0187, respectively). IL-10 and IL-17 levels did not differ between the study groups (p = 0.7273 and p = 0.6697, respectively). CONCLUSIONS: These results suggest that the cytokine profile and disease progression are altered by anti-congestive medications commonly prescribed for CCC.